Does Melissa officinalis consumption improve the salivary antioxidant status of smokers? - Sedigheh Bakhtiari; Zahara Yadegari; Poriya Ehyaei; Narges Gholizadeh (Babol University of Medical Sciences, 2020)
Background: The aim of this study was to investigate the effects of Melissa officinalis tea on the total antioxidant capacity of saliva among smokers. Methods: 24 smokers were selected by convenience sampling. Demographic information and duration of smoking were recorded at the beginning of study. Two cups of Melissa officinalis tea were given to the participants with specific instruction for 30 days. The unstimulated saliva was collected on first day, 15th and 30th days. Then, total antioxidant capacity was measured by a special kit. Statistical analysis was conducted by repeated measure ANOVA test. Results: The mean values of total antioxidant capacity of saliva was significantly higher in days 15 and 30 from the baseline. (p<0.0001, p=0.006). In day 30, the mean value of antioxidant was not significantly different from day 15. (p=0.271). Conclusion: Melissa officinalis tea consumption increase salivary antioxidants level in smokers.